计算(a+b-c)(a-b-c)-(a+b-c)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 08:26:54
计算(a+b-c)(a-b-c)-(a+b-c)^2计算(a+b-c)(a-b-c)-(a+b-c)^2计算(a+b-c)(a-b-c)-(a+b-c)^2原式=[(a-c)+b][(a-c)+b]-
计算(a+b-c)(a-b-c)-(a+b-c)^2
计算(a+b-c)(a-b-c)-(a+b-c)^2
计算(a+b-c)(a-b-c)-(a+b-c)^2
原式=[(a-c)+b][(a-c)+b]-[(a-c)^2+b]^2
=(a+c)^2-b^2-(a-c)^2+2b(a-c)-b^2
=2ab-2bc-2b^2
(a+b-c)(a-b-c)-(a+b-c)^2
=(a+b-c)(a-b-c-a-b+c)
=-2b(a+b-c)
=-2ab-2b^2+2bc
原式=[(a-c)+b][(a-c)-b]-[(a-c)+b][(a-c)+b](乘法分配律)
=[(a-c)-b-(a-c)-b][(a-c)+b]
=-2b[(a-c)+b]
=-2ab+2bc-2b^2
(a+b-c)(a-b-c)-(a+b-c)^2
=(a+b-c)[ (a-b-c)- (a+b-c) ]
=-2b(a+b-c)
计算(-a-b+c)(a+b-c)
计算:(a-2b+c)(a+2b+c)
计算(a+b+c)(a-b+c)在线等,
计算:(a-2b+c)(a+2b+c)
计算:(a-b+c¹)(-a+b-c¹)
计算a(a+b+c)(b-c)+b(a+b+c)(c-a)+c(a+b+c)(a-b)的值
计算(a+b-c)(a-b-c)
计算(a+b-c)(a-b-c)-(a+b-c)^2
计算(a+b-c)(a-b-c)-(a+b-c)^2
计算【(a-b+c)(a-b-c)+c²】/(a-b)=
已知向量(a*b)c=2,计算(a+b)*(b+c)*(c+a)
计算:(a+b-c)² -(a-b+c)(a+b-c).
计算(a-3b+c)(a+3b-c)-(a+3b+c)²
计算:a/[(a-b)(b-c)]+b/[(b-c)(b-a)]+c/[(c-a)(c-d)]
计算:(a+b+c)²
计算:(a+2b-c)²
计算(c-a)/(a-b)(b-c)+(a-b)/(b-c)(c-a)+(b-c)/(c-a)(a-b)
计算(a+b-c)(a+b+c)-【(a-b)²+4ab】